Skin delivery of 5-fluorouracil via ethosomes using microwave as skin permeation enhancement technique / Nauman Rahim Khan - Rahim Khan, Nauman (Institute of Graduate Studies, UiTM, 2017)
This project focused on formulation and investigation of interplay effects of ethosomes, ethanol and microwave for enhanced skin drug retention with minimal systemic absorption. The microwave was used to modify the skin barrier properties to enhance ethosomes and/or drug penetration/and drug retention which is detrimental to treat local malignant melanoma and to enhance patient compliance. Ethosomes are known to fuse with skin to enable local drug retention. Pre-treatment of skin with microwave and applying liquified medicine is deemed to “cement” the skin thereby raising skin drug deposition. 5-fluorouracil loaded ethosomes were prepared and subjected physicochemical characterization. The molecular characteristics of untreated, microwave and/or ethosomes and/or ethanol-treated skins were examined by ATR-FTIR and raman spectroscopy, DSC and SEM techniques. The skin drug retention was promoted using larger ethosomes with negative zeta potentials that repelled anionic lipids of skin and hindered vesicle and/or anionic drug penetration into deep layers. Due to low ethanol, they were less able to fluidize the lipid and defluidize the protein domains at epidermis to enlarge aqueous pores for drug permeation. Pre-treatment of skin by 2450 MHz microwave for 2.5 min further increased skin drug penetration and retention of E5 ethosomes and provided lower drug permeation than cases treated for 1.15 min and 5 min. Pre-treating skin with microwave fluidized lipid and defluidized protein domains of skin that promoted transdermal drug penetration…